A positive feedback loop reinforces the allergic immune response in human peanut allergy - Zhou, Xiaoying (J Exp Med, 2021)
Food allergies are a leading cause of anaphylaxis, and cellular mechanisms involving antigen presentation likely play key roles in their pathogenesis. However, little is known about the response of specific antigen-presenting cell (APC) subsets to food allergens in the setting of food allergies. Here, we show that in peanut-allergic humans, peanut allergen drives the differentiation of CD209(+) monocyte-derived dendritic cells (DCs) and CD23(+) (FcєRII) myeloid dendritic cells through the action of allergen-specific CD4(+) T cells. CD209(+) DCs act reciprocally on the same peanut-specific CD4(+) T cell population to reinforce Th2 cytokine expression in a positive feedback loop, which may explain the persistence of established food allergy. In support of this novel model, we show clinically that the initiation of oral immunotherapy (OIT) in peanut-allergic patients is associated with a decrease in CD209(+) DCs, suggesting that breaking the cycle of positive feedback is associated with therapeutic effect.